Метафоричний розвиток семантично підпорядкованого номінації земля поетоніма лан - Калинюк, Н.В. (Лексикографічний бюлетень, 2013)
The features of the use in the language of poetry of poetic nomination the field are outlined in the article. Paradigmatic and valency properties of nominative row with the rod component the field are studied. Frequency and actuality the use of lexeme the field, amount of the semantic, figuratively associative branchings in its using in the language of the Ukrainian poetry of ХХ of century is found out.